Restoring the growth potential of formerly centrally planned economies - Hubert Gabrisch (Intereconomics, 1991)
All formerly centrally planned economies record very substantial declines in their social products. The largest drops in production are recorded in Poland and in east Germany (the former GDR), that is, in those countries where the most radical steps towards a market economy were taken in 1990. Thus it looks as though a recession was unavoidable during transition. But what are the conditions that must be fulfilled in order to restore growth potential to these countries? The following article aims first to devise a theoretical picture of a successful transition. The criteria thus obtained are then employed for an analysis of the recessive processes in Poland, the first east European country to start a radical programme of transition. Finally, the recession in Poland is compared with that in the former GDR.
Keywords: 330